“Plan De Marketing Estratégico Para Aumentar La Adopción Y Fidelización De La Empresa TooshVip En La Ciudad De Loja - Malo Fajardo, Kevin Joel (2024)
This research aims to develop a strategic marketing plan to increase adoption and loyalty for the company TooshVip in the city of Loja. The purpose is to contribute to the development and positioning of the brand since TooshVip is currently a Small and Medium-sized Enterprise (SME) without a strategic marketing plan due to its recent market launch. This puts the company at a competitive disadvantage, lacking the necessary tools to achieve maximum adoption and loyalty from both potential and existing customers. The study is based on three specific objectives. Firstly, a situational analysis was conducted using the 4Ps of marketing, analyzing matrices such as internal and external factors, SWOT analysis, and the IE matrix. This helped determine the business situation. Secondly, a high-impact matrix was created to identify opportunities and threats facing the company and to establish objectives and strategies that will help position the brand more effectively. Finally, a proposal for the strategic marketing plan was developed, revealing that TooshVip has several opportunities in the market as a relatively new application that can expand into different areas. However, it also has more weaknesses than strengths because it lacks strategic plans, making it vulnerable to competition. Currently, 52% of potential customers are unfamiliar with the brand. In conclusion, it is recommended to implement the proposed marketing plan, improve and widely promote the brand to achieve a strong real and mental positioning in the Loja market. Additionally, designing sections within the application to broadcast advertisements from partners.